2017
DOI: 10.1080/01942638.2016.1261979
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reach-to-Grasp by School-Aged Children with Down Syndrome Elucidates Limitations in Upper Extremity Motor Control

Abstract: Motor control mechanisms that mediate both PP and execution of the fundamental RTG movement are potential factors limiting upper extremity activity in school-aged children with DS. They should be addressed in future intervention-based research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…According to the authors, this result is also directly associated with the reduced movement velocity commonly found as a compensatory pattern in DS. Moreover, even in cases for which the clinical evaluation is good, general joint stiffness during arm abduction contributes to poor coordination in individuals with DS, diminishing maximum and minimum joint angles (Valvano et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors, this result is also directly associated with the reduced movement velocity commonly found as a compensatory pattern in DS. Moreover, even in cases for which the clinical evaluation is good, general joint stiffness during arm abduction contributes to poor coordination in individuals with DS, diminishing maximum and minimum joint angles (Valvano et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that movements in these conditions require the greatest muscular forces (i.e., impulses), the authors contend that those with Down syndrome had difficulties applying the appropriate forces at movement onset (and making adjustments using feedforward control), and that online feedback-based control (i.e., limb-target control) was insufficient to minimize endpoint variability. Results from similar studies showed greater hand-INSIGHTS ON LIMB CONTROL FROM VARIOUS SPECIAL POPULATIONS 11 object contact velocities in children with Down syndrome during a reach-to-grasp task (Valvano et al 2017) and increased movement times for people with Down syndrome in integrated one-arm reversal tasks (Reilly et al 2017), which are indicative of deficits in force specification and insufficient feedback-based online control.…”
Section: Down Syndromementioning
confidence: 92%
“…As in previous work, the limb trajectories of adults with Down syndrome were characterized by longer movement times, lower velocities and multiple velocity peaks. In addition, their trajectories were more curved than the trajectories of people without Down syndrome, reflecting a less efficient movement path (see also Valvano et al 2017). The young adults with Down syndrome were also more dependent on proximal than distal musculature to move their arms (i.e., greater movement at the trunk and less at the elbow; see also, Anson and Mawston 2000).…”
Section: Down Syndromementioning
confidence: 96%